The state of the mucous membrane of the upper digestive tract in children with combined GERD and chronic gastroduodenal pathology - N.V. Kirianchuk (Zaslavsky O.Yu., 2019)
Background. The frequency of gastroesophageal reflux disease (GERD) in population is reported to be from 7 to 60 %, and in children it varies from 2-4 to 8.7-49 % according to various authors. In children, GERD often develops against a background of chronic gastroduodenal pathology. The purpose was to study the endoscopic picture of the upper digestive tract in children having combined lesions. Materials and methods. The study included 120 children with concomitant GERD and chronic gastroduodenal pathology. The diagnoses were verified with esophagogastroduodenoscopy. The children were divided into groups depending on the nature of the esophagus mucosa lesion. Group I included 35 children with erosive and ulcerative esophagitis; group II included 43 children with catarrhal esophagitis. Group III included 42 children with GERD without esophagitis. Results. The frequency of gastroesophageal reflux of the III degree is more common in children with combined GERD and erosive and ulcerative esophagitis. GERB without esophagitis develops more often in children with moderate hyperemia and edema in the gastric mucosa (p < 0.05). More pronounced inflammatory changes in the gastric mucosa are more often (p < 0.05) associated with gastroesophageal reflux with inflammatory lesions of the esophageal mucosa resulting in both catarrhal and erosive esophagitis. Destructive changes in the mucosa of the esophagus and duodenal cap do not correlate with each other. Conclusions. In children with combined GERD and chronic gastroduodenal pathology, the degree of severity of esophagitis depends on the nature of the lesion of the gastric mucosa and duodenum.